Observational Studies on Evaluating the Safety and Adverse Effects of Traditional Chinese Medicine. (14th September 2013) - Lai, Jung-Nein; Tang, Jin-Ling; Wang, Jung-Der
Abstract : Background . This study aims to share our experiences when carrying out observational studies of traditional Chinese medicine (TCM). Methods . We have proactively monitored the safety profiles of Duhuo Jisheng Tang (DJT), Suan Zao Ren Tang (SZRT), and TMN-1. A list of adverse events (AEs), complete blood counts, and liver and kidney function tests were obtained from the participants during their scheduled hospital visits. Retrospective observational studies were conducted based on the reimbursement database of the National Health Insurance system, Taiwan, to explore the relationship between the use of TCM that have been adulterated by aristolochic acid and the risk from both nephrotoxins and carcinogens. Results . A total of 221, 287, and 203 AEs were detected after SZRT, DJT, and TMN-1 had been taken, respectively. Dizziness, headache, stomach ache, and diarrhea were judged to be probably related to SZRT treatment. Retrospective observational studies found an association between the consumption of aristolochic acid-containing Chinese formulae such as Mu Tong and an increased risk of CKD, ESRD, and urinary tract cancer. Conclusion . Prospective and retrospective observational studies seem to have specific advantages when investigating the safety and adverse effects of TCM therapies, as well as possibly other alternative/complementary therapies.